From Utility Value To Sign Value: Student Consumerism In Digital Capitalism And The Negotiation Of Religious Values - Sabaruddin; Bahtiar; Mutmainnah (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This study analyzes the construction of consumption behavior among dormitory students amid the expansion of digital advertising, the rise of consumer culture, and the role of religion and educational institutions as normative mechanisms. Using a qualitative descriptive-analytical design, data were collected through observation and in-depth interviews with boarding house students who actively use social media and online shopping platforms. The analysis combines Jean Baudrillard’s perspective on consumer society, Pierre Bourdieu’s concept of habitus, and Max Weber’s theory of rational action to examine consumption dynamics at micro, meso, and macro levels. The findings reveal that digital advertising not only delivers product information but also produces meanings that shape students’ preferences, lifestyles, and social identities. Intensive exposure to advertising, combined with technological adaptability and a phase of self-discovery, shifts consumption orientation from utility value to symbolic value. Consumption becomes a strategy for gaining social recognition and constructing self-image. However, students are not merely passive consumers; they evaluate ratings and reviews, consider financial limitations, and even transform into digital economic actors such as resellers. At the same time, tensions emerge between value-oriented rationality derived from religion and education and the instrumental rationality promoted by the digital market system, which may lead to impulsive buying, wastefulness, and financial strain. This study contributes by positioning boarding house students as active agents negotiating within digital capitalism and recommends strengthening financial and media literacy alongside the internalization of religious consumption ethics.